Análise das sequências de nucleotídeos de novos subtipos de toxinas e proteínas de anêmonas do mar por sequenciamento de RNA de nova geração - Boralli, Leandro Augusto Freire [UNIFESP] (2017)
Sea anemones are sessile organisms that employ a venomous apparatus (preferably located in their tentacles) to produce and inoculate paralyzing toxins in their prey or to defend themselves. Our group recently contributed to the characterization of the peptidoma of 3 species of sea anemones, showing that the molecular diversity of the toxins of these organisms is much higher than expected. From the point of view of the nucleotide information obtained from anemones, few species were investigated in detail, revealing that at the moment only a small fraction of the toxic arsenal of the cnidarians was investigated. In addition, new structural proteins that occur in anemones present structural and genetic similarity to proteins of derived organisms, such as vertebrates. In this sense, we intend to analyze and compare the transcriptome of two populations of the Brazilian anemone Bunodosoma caissarum, a population of the São Paulo coast and another population located in the isolated São Pedro and São Paulo archipelago. This analysis will be done through the sequencing of new generation RNA, by the Illumina system. With this sequencing and with bioinformatics analyzes we hope to find information regarding new toxins never before studied in this species and also to analyze the differences in the expression profile between the two populations